Barriers to timely identification of bipolar disorder in youth: a multidimensional perspective - Keramatian, Kamyar; Morton, Emma (Frontiers in Child and Adolescent Psychiatry, 2023)
Bipolar disorder (BD) in youth often goes unrecognized and therefore untreated. However, little is known about pathways to treatment of youth with BD and factors that influence the time taken for each stage of these pathways. In this article, we use the conceptual framework by Scott and colleagues called the Model of Pathways to Treatment as a foundation to explore the components of delay in the diagnosis and treatment of youth with BD. The total time from the onset of symptoms until treatment initiation was divided into four sequential intervals; i.e., the Appraisal, the Help-seeking, the Diagnostic and the Pre-treatment intervals and potential disease, patient, and healthcare system/provider factors that influence each interval were identified. This multidimensional conceptual framework can offer a systematic approach to understanding and exploring barriers to early identification and interventions in BD, which is a crucial step in the development of strategies to facilitate prompt diagnosis and treatment. We hope this work contributes to the discussion on delayed diagnosis and treatment of youth with BD and provides a roadmap to inform future research studies and policy decisions.